Fault identification and fault location methods for VSC-HVDC transmission lines based on the traveling waveform difference. (May 2023) - Liu, Tianqi; Zhang, Yuhan; Wang, Shunliang; Li, Xiaopeng; Gooi, Hoay Beng; Ghias, Amer M.Y.M
Highlights: The backup protection including fault identification and location methods is proposed for VSC-HVDC transmission lines. The waveform difference in same/different-mode traveling waves between faulty and unfaulty lines is elaborated in theory. The protection can identify the double-pole-to-ground fault with unequal positive and negative pole fault resistances. The waveform difference between 1-mode differential forward and backward currents can locate faults rapidly and accurately. The methods can improve the protection selectivity, reliability, rapidity, and sensitivity. Abstract: Due to the low-damping characteristic of the voltage source converter based high voltage direct current (VSC-HVDC) transmission system, the line current will reach the peak value within a few milliseconds after DC fault, threatening the safety of power electronic devices. Therefore, a reliable and rapid protection scheme comprising fault identification and location is necessary. The detection time cost of traditional backup protections is high. Worse still, most existing methods cannot distinguish the double-pole-to-ground fault with unequal positive and negative pole fault resistances. To solve the issues, a backup protection based on the same/different-mode traveling wave, differential forward/backward current, and traveling waveform difference for VSC-HVDC lines is proposed in the paper. The fault characteristics of same/different-mode traveling wave and relationship between fault distance and differential forward/backward current are elaborated. The waveform differences in positive/negative-pole same/different-mode traveling waves and 1-mode differential forward/backward currents are summarized. According to these analyses, the protection is established and the VSC-HVDC is modeled in PSCAD. Based on the sufficient simulation tests, it is verified the proposed fault identification and location schemes have great performance, with superiority in fault resistance and distance tolerance (2, 000 Ω and the whole line), strong anti-interference capability, fast fault distinguishment, and accurate fault location.